Implementation of The K-Mean Algorithm for Data Clustering in Alumni Data Information Systems - Agus Sifaunajah; Muhyiddin Zainul Arifin; Habib Qoirul Tabiin (NEWTON: Networking and Information Technology, 2022)
Graduates are the most important parameter of an organization, alumni are also active for a formal or informal educational organization or institution. In this era of big data, the correct and fast management of alumni data can bring significant benefits to the institution concerned. Algorithm K-means Clustering is one of the data collection algorithms that ranks data quite well. Using a research method, the Research and Development (R&D) department will try, as far as possible, to produce works that can be used to test real, not just hypotheses or theories.